Minimum Legal Drinking Age and Educational Outcomes - Manuel Bagues; Carmen Villa (Institute of Labor Economics (IZA), 2024)
Over the past decades, many European countries have raised the minimum legal drinking age (MLDA) from 16 to 18 years. This study provides novel evidence of the impact of this policy on educational outcomes by exploiting the staggered timing of MLDA changes across Spanish regions. Raising the MLDA decreased alcohol consumption among adolescents aged 14–17 by 8 to 18% and improved their exam performance by 4% of a standard deviation. This effect appears driven by alcohol's direct impact on cognitive ability, as we find no significant changes in potential mediators like use of other substances or time spent on leisure activities, including socialising, sports, gaming, or internet use. We also observe a decrease in tranquilliser and sleeping pill use, suggesting improved mental health. Our findings indicate that reducing teenage alcohol consumption represents a significant opportunity to improve educational outcomes in Europe, where youth drinking rates remain notably high.
Keywords: I18; I12; I21; 330; alcohol; adolescence; minimum legal drinking age; PISA